Faktor yang Berhubungan dengan Deformitas Kaki pada Penyandang Diabetes Melitus Tipe 2 - Desi Susanti; Dita Amita (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to explain the factors associated with foot deformity in people with type 2 diabetes. This study used a descriptive-analytic method with a cross-sectional design. The results showed that the aspects related to the incidence of foot deformity were education (P=0.022; OR=4.57), body mass index (BMI) (P=0.035; OR=0.23), and knowledge (P=0.001). ; OR = 9.17), while the factors of age (P = 0.22) and gender (P = 0.712) were not associated with the incidence of foot deformity. In conclusion, the knowledge factor is a factor that can influence nine times more strongly the incidence of foot deformity in people with type 2 DM compared to other factors. Keywords: Foot Deformity, Diabetes Mellitus